AB1114 Patient's self-monitoring of disease activity of rheumatic diseases via webapp – study design, patient's perspective and recruitment in the first 11 months of the swiss multicentre, longitudinal compass ii study. (15th June 2017) - Jaeger, VK; Schiffer, P; Zufferey, P; Pichler, L; Badaracco, A; Walder, M; Dudler, J; Frey, D; Müller, F; Walker, UA
Abstract : Background: The management of patients with rheumatic diseases is guided in part by asking patients about their medical history at each clinic visit. Patients often find it difficult to accurately remember the course of their symptoms between these appointments as they are often months apart. Regular app-based patients' self-monitoring of disease activity (with our without feedback to the rheumatologist) between clinic visits might provide a possible solution for this. The COmPASS I study [1] demonstrated that RA patients' self-assessments of disease activity via App correlate strongly with rheumatologists' assessments. Following up on this, the Swiss based COmPASS II study is embedded in the Swiss rheumatology registry (SCQM) and hence allows the linkage of data obtained via the COmPASS II App from the patients with routine clinical data collected in the registry. The main aims of the COmPASS II study are to assess if continuous self-monitoring of the disease by patients optimises disease management and outcome in rheumatic diseases, and to assess the fluctuation of disease activity between clinic visits. Objectives: The objectives of this abstract are to describe the set-up and the recruitment of the COmPASS II study in the first 11 months. Methods: The COmPASS II App questionnaire consists of the RAPID3 score, a validated, commonly used PRO to self-assess disease activity. Additionally, patients are asked about their therapy compliance and cortisone dose. At inclusion, interested patients with RA, axSpA and PsA are electronically randomized into 3 study arms (Figure 1 ). In arm 1 patients and rheumatologist are displayed the self-assessed disease activity over time, the patient directly via the App and the rheumatologist via the SCQM registry. In arm 2 only the patients are displayed their disease activity chart and in study arm 3 neither sees the recorded data. Patients are encouraged to fill in the App weekly. Results: The COmPASS II App went online on the 15/02/2016. In the first 11 months of COmPASS II, 272 patients were enrolled by their rheumatologist. 64% of patients used the WebApp (32% in arm 1, 38% in arm 2 and 30% in arm 3); 82% of patients filled in the questionnaires for longer than a months, the longest follow-up was 11 months. On average patients use the App every 2 weeks. Patients found the App easy to use "The COmPASS II WebApp is so easy to use. It doesn't even take me 2 min." and received feedback included "Now my rheumatologist sees how I was since the last appointment instead of me trying to remember how I was half a year ago.". Conclusions: The COmPASS II study will validate the utility of app-based patients' self-assessments in enhancing disease control in a treat to target approach and deliver numerous additional scientific data. References: Mueller R et al. Patient's Self-Monitoring Via Smartphone: The Compass Study - COrrelation between PAtient self-ASSessment of rheumatoid arthritis disease activity via smartphone technology and physicians' validated scores [abstract]. Arthritis Rheumatol. 2014;66(S10). Acknowledgements: COmPASS II is supported by an unrestricted grant from AbbVie. Disclosure of Interest: None declared